The Effect of the Swedish Payroll Tax Cut for Youths on Firm Profitability - Malm, Arvid; Eklund, Johan; Francis, David; Jiang, Nan (World Bank, Washington, DC, 2016)
Payroll taxes in Sweden were reduced substantially for people ages 26 years or younger on July 1, 2007. The objective of this tax cut was to lower youth unemployment. The question of how gains from payroll taxes are distributed between workers and owners of firms has been the focus of considerable theoretical and empirical attention. This paper examines the impact of the Swedish reform on firm profits using individual-level and firm-level microdata. Previous investigations into the effects of this particular reform have focused entirely on the effects on employment and wages, or have been limited to the retail sector. This paper finds that the reform was not associated with a general increase in firm profitability, but that there is some evidence of a positive effect on profits in the retail and wholesale sector.